Penerapan Manajemen Mutu Terpadu (TQM) terhadap Kualitas Pelayanan di Tengah Masa Pandemi Covid-19 - Levina Isnanti Rachmania Hernanda; Muslimin Muslimin (Journal of Management and Bussines (JOMB), 2022)
This research is to find out how much influence the implementation of TQM has on service quality in the midst of the COVID pandemic at Husada Prima Surabaya Hospital. The research method is quantitative data. This study uses primary data by distributing questionnaires to 165 respondents. The results showed, a) the focus variable on the patient has a significance probability value of 0.784. This indicates that the significance probability value is > 0.05; b) the variable obsession with quality has a significance probability value of 0.464. This indicates that the significance probability value is > 0.05; c) the continuous system improvement variable has a significance probability value of 0.193. This indicates that the significance probability value is > 0.05; d) education and training variables have a significance probability value of 0.628. This indicates that the significance probability value is > 0.05. Conclusion, a) the application of focus on patients has a positive effect on service quality; b) obsession with quality has a negative effect on service quality; c) continuous system improvement has a negative effect on service quality; d) education and training have a positive effect on service quality. Keywords: COVID-19, Service Quality, Integrated Quality Management, Hospital